Diversification of energy poverty in Central and Eastern European countries - Joanna Mazurkiewicz; Piotr Lis (Virtual Economics, 2018)
Household energy security, and in particular affordability of energy services and the energy poverty issue, is a debated topic both at the EU level and at the level of individual countries. The aim of the paper is to investigate the energy poverty diversity in the Central and Eastern European countries. The energy poverty index that aggregates three aspects: availability and affordability of energy services, as well as household energy efficiency, has been presented. This framework allows for comparison between countries and discloses the diversity of their energy poverty profiles. Analysis of energy poverty indicates diversification of level and dynamics of this phenomenon in the studied countries. Among countries of Central and Eastern Europe, there are both countries, where the problem of energy poverty is the highest, and the lowest in Europe. Almost all studied group is characterized by decreasing level of energy poverty in that particular period. Analysis of index components indicates diversification of energy poverty profiles. Important factor shaping the ability to acquire energy services was also the consequence of economic crisis, especially lowering the level of incomes and the increase of energy prices as a result of increasing tax burdens imposed on energy carriers.